Water/fat‐resolved whole‐heart Dixon coronary MRA: An initial comparison. Issue 1 (7th February 2013) - Börnert, Peter; Koken, Peter; Nehrke, Kay; Eggers, Holger; Ostendorf, Peter
<x xml:space="preserve">Abstract</x> Purpose To improve coronary vessel visualization in whole‐heart coronary magnetic resonance angiography (CMRA), fat suppression is typically applied. However, recent studies have shown that cardiac fat can also have diagnostic value. To enhance CMRA image quality by improved fat suppression and to provide additionally fat‐only information highly resolved, dual‐echo Dixon CMRA approaches have been developed. Methods In this pilot study, approved by the institutional review board, 30 patients were investigated comparing whole‐heart T1‐weighted dual‐echo Dixon CMRA to conventional whole‐heart fat‐suppressed balanced fast field echo CMRA, integrated into a routine clinical protocol that includes the administration of gadolinium for perfusion and late enhancement measurements. Signal‐to‐noise‐ratio, contrast‐to‐noise‐ratio, and image quality were analyzed. Results Dual‐echo Dixon significantly (P<0.000001) improved image quality compared with conventional fat‐suppressed balanced fast field echo CMRA. Signal‐to‐noise‐ratio and contrast‐to‐noise‐ratio were found to be comparable when balanced fast field echo was performed before gadolinium and dual‐echo Dixon fast field echo after gadolinium administration. Conclusion Dual‐echo Dixon can help to improve whole‐heart CMRA image quality significantly. The additional whole‐heart fat information delivered by this approach can support a number of new clinical studies addressing the diagnostic and the predictive value of intramyocardial and extramyocardial fatty deposits. Magn Reson Med 71:156–163, 2014. © 2013 Wiley Periodicals, Inc.